Cape Verde : 2010 Article IV Consultation and Request for a 15-Month Policy Support Instrument-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2010)
Cape Verde has demonstrated notable economic and policy resilience. The public investment program should be completed, but new external borrowing should be limited to restore fiscal buffers. The monetary policy framework could be improved in the medium term. The Bank of Cape Verde should step up efforts to safeguard the financial system and to develop the government securities market. Improving economic and financial statistics to facilitate better monitoring and analysis of developments to guide policy formulation is needed in Cape Verde.